The contribution of elevated foetal haemoglobin levels to a relatively mild clinical phenotype in Turkish Cypriot patients with ?-thalassaemia - Terali, K.; Ozkan, O. C.; Cetin, O.; Ugurlu, K. C.; Akdeniz, E. (Wiley-Blackwell, 2016)
[Abstract Not Available]
41st FEBS Congress on Molecular and Systems Biology for a Better Life -- SEP 03-08, 2016 -- Kusadasi, TURKEY